(untitled) (Global Journal of Medical Research, 2023)
Cancer disease results from mutations leading to apoptosis failure and immune system dysfunction Because one in two people in developed counties will be diagnosed with cancer in their lifetimes cancer and metastasis prevention should be ahead of therapies The immune system in cancer patients is compromised and can be fixed with a reboot The major oncofetal protein alpha-fetoprotein can deliver toxins instead of nutrients to the immune suppressor cells and kill them The death of myeloid suppressor cells unleashes the immune attack on cancer cells cancer stem cells and metastases Injectable and oral formulations of alphafetoprotein with toxins provide an opportunity to prevent and treat the disease